Naturalizing digital immigrants : the power of collegial coaching for technology integration - Alaniz, Katie; Wilson, Dawn K. (Dawn Kathleen) (Rowman & Littlefield, 2015)
This guidebook details the process of collegial coaching for technology integration within educational environments and is intended for use within a variety of settings, from primary classrooms through high schools to graduate educational leadership and instructional technology courses and beyond.